Who benefits more from supply chain alliances? Customers or suppliers - Xia, Yun; Xu, Xin; Liu, Ying; Zhang, Yanjiang (Technological and Economic Development of Economy, 2024)
Existing research provides limited evidence on the impact of supply chain relationships on the financial performance of upstream and downstream firms. Taking the recent proliferation of supply chain alliances between Chinese listed companies as an opportunity, we study the impact of supply chain alliances on the performance of customers and suppliers as well as the underlying mechanisms at play. We focus on Chinese A-share listed companies from 2001 to 2021 and use announcements issued by the listed companies to identify whether they have established a supply chain alliance with another listed company. The announcements come from the information disclosure system of listed companies of the Shenzhen Stock Exchange and the Shanghai Stock Exchange. Finally, we obtained 148 pairs of supply chain alliances which formed by 231 listed companies and involved 296 announcements of supply chain alliances. By using the propensity score matching method and difference-in-differences regressions, we find that supply chain alliances can alleviate friction between customers and suppliers and significantly improve the efficiency of working capital used by both customers and suppliers. Supply chain alliances increase suppliers’ inventory turnover and accounts receivable turnover, and reduce cash holdings, while supply chain alliances improve customer raw material turnover, and reduce accounts payable turnover. Moreover, the economic impact of supply chain alliances on customers and suppliers is asymmetric. Suppliers benefit more from alliances relative to customers, as evidenced by significant improvements in their financial performance and significantly reduced performance volatility. The “inherent differences” in market power and market value between customers and suppliers can have considerable asymmetries on economic consequences. We divide firms in a pair of supply chain alliances by market power and market value. The magnitude of the financial performance accruing from an alliance is considerably higher for the lower-market-power firm than for the higher-market-power firm. The magnitude of the financial performance accruing from an alliance is considerably higher for the lower-market-value firm than for the higher-market-value firm. Additionally, vertical supply chain alliances can significantly improve firm performance and reduce performance volatility compared to horizontal supply chain alliances. This paper provides new empirical evidence for our insight into the economic consequences of supply chain alliances and their boundary conditions.